Analisis Terkait Penerapan Peraturan Presiden Nomor 8 Tahun 2023 Tentang Pengelolaan Benda Muatan Kapal Tenggelam - Nabila Annisa Rafiq (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This research aims to analyze the implementation of Presidential Regulation Number 8 of 2023 concerning the Management of Sunken Shipwrecks (BMKT) in Indonesia. Indonesia as an archipelagic country has many sunken ship relics of high historical and cultural value. However, the existing regulations are considered to prioritize aspects of economic utilization over the protection of underwater cultural heritage. This research uses normative juridical method with statutory and conceptual approaches. The results of the analysis show that Presidential Regulation 8 of 2023 has not explicitly regulated the protection of BMKT and sanctions against illegal actions, resulting in weak supervision and many cases of unauthorized BMKT removal. In addition, education and counseling to the public regarding the importance of protecting BMKT is still very minimal. Therefore, it is necessary to establish a special law and increase counseling so that BMKT can be protected as a cultural heritage for future generations.